PENGEMBANGAN PENELITIAN TINDAKAN KELAS VIRTUAL LEARNING ECONOMI - Husnaini, Husnaini; Widianti, Santi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstrakâ€” This research was conducted with the aim of assisting teachers in carrying out classroom action research in virtual learning economi. Some of the obstacles experienced by economi teachers in delivering material to students include the educational background of participants who come from outside the department of pure economi or the department of economi education, so they are less able to provide subject matter properly. The method used in this study is the method of implementing this activity by means of Focus Group Discussion (FGD) and continued with the practice of Virtual Learning and CAR. There were 15 economi teacher participants from several schools. The results of this activity in the form of (a) mapping the topic of high school sociology material, (b) increasing the basic knowledge of teachers one of which gives insight into material knowledge, methods and models of economi learning, gives insight into material knowledge of virtual learning skills (learning houses), gives insight into material knowledge classroom action research, (c) the practice of introducing the basic use of virtual learning media "home learning", (d) the simple practice of making a PTK proposal, (e) a follow-up plan (f) making a PTK report.Â Keywordsâ€” Classroom Action Research, Virtual Learning EconomiÂ Abstractâ€” Â Penelitian ini dilakukan dengan tujuan untuk membantu guru dalam melaksanakan penelitian tindakan kelas virtual learning economi. Beberapa kendala yang dialami oleh guru ekonomi dalam menyampaikan materi kepada peserta didik diantaranya yaitu latar belakang pendidikan peserta yang berasal dari luar jurusan ekonomi murni ataupun jurusan pendidikan ekonomi, sehingga kurang mampu memberikan materi pelajaran dengan baik. Metode yang digunakan dalam penelitian ini yaitu Metode pelaksanaan kegiatan ini dengan cara Focus Group Discussion (FGD) dan dilanjutkan dengan praktik Virtual Learning dan PTK. Peserta kegiatan berjumlah 15 orang guru ekonomi yang berasal dari beberapa sekolah. Hasil dari kegiatan ini berupa (a) pemetaan topik materi ekonomi SMK, (b)peningkatan pengetahuan dasar guru salah satunya memberi wawasan pengetahuan materi, metode dan model pembelajaran ekonomi, memberi wawasan pengetahuan materi keterampilan virtual learning (rumah belajar), memberi wawasan pengetahuan materi penelitian tindakan kelas, (c) praktik pengenalan dasar penggunaan media belajar virtual learning â€œ rumah belajarâ€, (d) praktik sederhana pembuatan proposal PTK, (e)rencana tindak lanjut, (f) pembuatan laporan PTK.Â Kata Kunciâ€” Penelitian Tindakan Kelas, Virtual Learning Economi